2015
DOI: 10.1039/c5tc02576a
|View full text |Cite
|
Sign up to set email alerts
|

Star-shaped triphenylene discotic liquid crystalline oligomers and their hydrogen-bonded supramolecular complexes with simple acids

Abstract: The synthesis and self-assembly properties of four novel star-shaped oligomers containing triphenylene discotic mesogens are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…The absorption spectra (see ESI, Figure S15) of TP1Br and TP2Br precursors display two main absorption maxima (λ abs ) at 280 and 310 nm which are assigned to the π-π* and n-π* transitions from the TP fragments, respectively. 84 As expected, the absorption measured for TP2Br is twice the one measured for TP1Br. Due to the high absorption coefficient of the TP cores and the low one of the cluster core in the same area, absorption spectra of Cplx1 and Cplx2 are similar to the absorption spectra of TP1Br and TP2Br.…”
Section: Photophysical Properties In Solutionsupporting
confidence: 78%
“…The absorption spectra (see ESI, Figure S15) of TP1Br and TP2Br precursors display two main absorption maxima (λ abs ) at 280 and 310 nm which are assigned to the π-π* and n-π* transitions from the TP fragments, respectively. 84 As expected, the absorption measured for TP2Br is twice the one measured for TP1Br. Due to the high absorption coefficient of the TP cores and the low one of the cluster core in the same area, absorption spectra of Cplx1 and Cplx2 are similar to the absorption spectra of TP1Br and TP2Br.…”
Section: Photophysical Properties In Solutionsupporting
confidence: 78%
“…Columnar discotic liquid crystals(DLC) possessing polycyclic aromatic cores are well known as mesophase semiconductors, [51][52][53][54][55] the discotic column formed by the stacked aromatic cores functiona se lectron transport pathways with the one-dimensional features of am olecular wire, whereas the peripheral alkyl chains serve as insulators. DLC semiconductors are presently being investigated as active materials in printed organic thin-film devices,s uch as organic photovoltaic solar cells (OPV), [56] organic field-effect transistors (OFET), [26] and organic light-emitting diodes (OLED).…”
Section: Chargecarrier Mobility By Time-of-flight (Tof) Techniquementioning
confidence: 99%
“…The DSC curves of TM1 exhibited two endothermic transitions at 115.3 and 164.0 °C upon heating and two exothermic transitions at 137.4 and 118.1 °C upon cooling (Figure b). POM results indicated that a typical masaic texture was observed when slow cooling to 137.0 °C, indicating a possible hexagonal columnar liquid crystalline phase (Figure a) ,. Upon further cooling to 118.4 °C, the liquid crystals began to crystallize into brick‐like crystals with large boundary (Figure a) .…”
Section: Resultsmentioning
confidence: 99%